PERSEPSI PETANI TERHADAP KERJASAMA PENGELOLAAN LAHAN REHABILITASI TAMAN NASIONAL MERU BETIRI - Rizki Fitriyan Hariyadi; Luh Putu Suciati (UNEJ e-Proceeding, 2018)
This study aims to determine the perceptions of farmers in collaborating on the rehabilitation of Meru Betiri National Park. ) The chosen location is in the Reubetiri National Park Rehabilitation Zone in Wonoasri Village, Tempurejo District, National Park Management Section (SPTN) II, Meru Betiri National Park. The consideration in choosing a location is because the area is one of the locations of the PE program (Ecosystem Recovery). The research method used is descriptive-analytic method. The method of data collection is done by interviewing using questionnaires, observation and documentation. Respondents in this study were 40 farmers who collaborated in rehabilitation land management. Data analysis used a scoring analysis of perceptions of farmers in collaborative rehabilitation of land management. The results showed the overall level of perceptions of farmers obtained a value of 76.51 which means included in the good category. In the four indicators there are several differences in the assessment of each indicator, where the indicator of the cooperation mechanism is in the good category of 12.6, then the benefit indicator of cooperation falls into the fairly good category of 8.75. While the indicators of farmers 'obligations are in the good category, which is 38.33, then the indicators of the farmers' rights are also in the good category, which is 16.83. Although farmers 'perceptions of collaborative rehabilitation management show a good category, however, farmers' awareness of cooperation agreement is still relatively low due to the fact that many farmers intentionally still violate a number of rules that have been mutually agreed upon between farmers and national parks. Like the example of removing and deliberately treating trees or seeds that are planted so that the plants die, because they assume that if the main plants grow well, the canopy of the leaves will cover annual crops or intercropping so that the growth is not good, the yield is not optimal and their income decreases